Defending Their Own in the Cold : The Cultural Turns of U.S. Puerto Ricans - Zimmerman, Marc, 1939- (Book collections on Project MUSE., 2011)
This volume explores US Puerto Rican culture as presented in East Coast, Midwest, and Chicago cultural production while exploring Puerto Rican musical, film, artistic and literary performance. Marc Zimmerman relates the experience of Puerto Ricans to that of Chicanos and Cuban Americans.